Kontribusi Layanan Administrasi Sarana Prasarana Dan Bimbingan Konseling Terhadap Kepuasan Siswa Di SMP Batik Surakarta - PUTRI, Meyka Sari; , Prof. Dr. Sutama, M.Pd; , Dr. Sabar Narimo, M.M., M.Pd (2015)
World of education has the function of producing qualified workforces for numerous kinds and levels of skills. In accordance to that issue educational institution must prepare adequate facilities. Besides that, services given also must give support in order to achieve optimal education. Students' satisfaction is one of the characteristic of qualified school, thus it better for education institution to pay attention the satisfactory of the students. The purpose of the research is to test is there any contribution of facility and infrastructure, administration and guidance counseling toward students' satisfaction in Batik Surakarta junior high school both simultaneously and partially. This research is qualitative research with Batik Surakarta junior high school's students as the population, and using sample as much as 189 students. Data collecting method is by questionnaire, interview, and documentation. Questionnaire instrument is tested its validity using product moment correlation and the reliability test is by using alpha cronbach. Data obtained will be analyzed statistically by F test and partially by using t test. F test can be conducted by comparing F count and F table, if f count > f table, (Ho is rejected and Ha is accepted). T test is known with partial test which is to test how the effects of each independent variable are by itself alone toward its dependent variables. This test can be done by comparing t count and t table or by seeing the significant columns in each t count, identical t test with f test process. Test result (f test) shows that administration service, infrastructure service and guidance counseling together contribute significantly toward students' satisfaction. The level of determination coefficient or R square = 0.427 and p = 0.000 which means that the influence administration service, infrastructure service and guidance counseling variables toward students' satisfaction is as much as 42.7%. While the t test performed shows that the administration service partially contributes significantly toward students' satisfaction with the t count is 5.610 with significance p = 0.000, because the value of p < 0.01. Infrastructure partially contributes significantly toward students' satisfaction. The analysis result shows that t count is 5.563 with significant level p = 0.000, because the value of p < 0.01. Guidance counseling service contributes significantly toward students' satisfaction. The analysis result of t count value is 4.702 with significance p = 0.00, because p<0.01.